ELEMENTS OF BIOCLIMATOLOGICAL CHARACTERISTICS OF VRANJSKA SPA - Stevanović, Vladica (Bulletin of Natural Sciences Research, 2019)
Bio-climatological analysis of Vranjska spa, based upon the equivalent temperatures (Teq) and Charles method (vapor weight), along with anthropo-climatic classification of Kruger, updated and adjusted, served as means of determining bio-climatological characteristics. Equivalent temperatures have been calculated for the period between 1985 and 2005, for the meteorological station Vranje, placed into six bio-climatological classes and three weather types. Representative weather types are cold (5.0 °C < Теq < 22.0 °C), agreeable (22.0 °C < Теq < 50.0 °C) and overheated (50.0 °C < Теq < 70.0 °C) with following classes: cold, algid, cool, agreeable, warm, humid and sultry.